Focal dystonia in musicians: linking motor symptoms to somatosensory dysfunction - Konczak, Juergen; Abbruzzese, Giovanni (Frontiers in Human Neuroscience, 2013)
Musician’s dystonia (MD) is a neurological motor disorder characterized by involuntary contractions of those muscles involved in the play of a musical instrument. It is task-specific and initially only impairs the voluntary control of highly practiced musical motor skills. MD can lead to a severe decrement in a musician’s ability to perform. While the etiology and the neurological pathomechanism of the disease remain unknown, it is known that MD like others forms of focal dystonia is associated with somatosensory deficits, specifically a decreased precision of tactile and proprioceptive perception. The sensory component of the disease becomes also evident by the patients’ use “sensory tricks” such as touching dystonic muscles to alleviate motor symptoms. The central premise of this paper is that the motor symptoms of MD have a somatosensory origin and are not fully explained as a problem of motor execution. We outline how altered proprioceptive feedback ultimately leads to a loss of voluntary motor control and propose two scenarios that explain why sensory tricks are effective. Sensory tricks are effective, because the sensorimotor system either recruits neural resources normally involved in tactile-proprioceptive (sensory) integration, or utilizes a fully functioning motor efference copy mechanism to align experienced with expected sensory feedback. We argue that an enhanced understanding of how a primary sensory deficit interacts with mechanisms of sensorimotor integration in musician’s dystonia provides helpful insights for the design of more effective behavioral therapies.